(untitled) (Research, Society and Development, 2021)
The objective of the present study is to report experience about the identification of nursing diagnoses related to depression in the elderly in Primary Care, as well as to highlight the importance of nursing care for the promotion of elderly health. A descriptive, descriptive study, with a qualitative approach, carried out by the academics from the Federal University of Pará. The study was developed during nursing consultation with an elderly person, in a Basic Health Unit (UBS), located in the municipality of Belém-Pa. The Geriatric Depression Scale and the NANDA were used to identify the nursing diagnoses. As the results of the depression scale, the elderly can be classified as a mild depression. The diagnoses found are: anxiety, fear, stress and impaired memory. It is evident the importance of the nursing diagnosis in the identification of depression in the elderly, especially when the patient is a member of the Basic Health Unit (UBS), since these professionals can use nursing consultations.